자동-레이블링 기반 영상 학습데이터 제작 시스템 - 이용(Ryong Lee); 장래영(Rae-young Jang); 박민우(Min-woo Park); 이건우(Gunwoo Lee); 최명석(Myung-Seok Choi) (한국콘텐츠학회 논문지, 21(6), 2021)
The drastic advance of recent deep learning technologies is heavily dependent on training datasets which are essential to train models by themselves with less human efforts. In comparison with the work to design deep learning models, preparing datasets is a long haul; at the moment, in the domain of vision intelligent, datasets are still being made by handwork requiring a lot of time and efforts, where workers need to directly make labels on each image usually with GUI-based labeling tools. In this paper, we overview the current status of vision datasets focusing on what datasets are being shared and how they are prepared with various labeling tools. Particularly, in order to relieve the repetitive and tiring labeling work, we present an interactive smart image annotating system with which the annotation work can be transformed from the direct human-only manual labeling to a correction-after-checking by means of a support of automatic labeling. In an experiment, we show that automatic labeling can greatly improve the productivity of datasets especially reducing time and efforts to specify regions of objects found in images. Finally, we discuss critical issues that we faced in the experiment to our annotation system and describe future work to raise the productivity of image datasets creation for accelerating AI technology. 최근 딥러닝 기술의 급속한 발전과 함께 학습데이터가 크게 주목을 받고 있다. 일반적으로 딥러닝 방식에서는 모델을 훈련시키기 위해 충분한 학습데이터가 준비되어 있어야 한다. 하지만, 딥러닝 모델 설계 작업과 달리 데이터셋을 제작하는 데 상당한 시간과 노력이 필요하다. 영상 데이터를 주로 다루는 시각지능 분야에서도 학습데이터 제작자들은 전문적인 학습데이터 제작 도구를 사용해 이미지 단위로 레이블링을 수작업으로 하고 있어 여전히 많은 시간과 노력이 필요한 상황이다. 따라서, 다양한 분야에서 필요한 충분한 영상 학습데이터셋을 확보하기 위해 기존의 수작업 방식을 대체할 수 있는 레이블링 기술이 필요하다. 본 논문에서는, 영상 학습데이터셋 동향을 소개하고, 학습데이터 제작 환경에 대해 분석한다 특히, 수작업으로 이루어지는 반복적이고 수고스러운 레이블링 과정을 자동화하여, '확인과 수정'의 단계를 비약적으로 단축시킬 수 있는 '스마트 영상학습데이터 제작 시스템'을 제안한다. 그리고, 실험을 통해 영상 학습데이터 제작 과정에서 이미지에 박스형 및 폴리곤형 객체영역을 지정하여 레이블링하는 데 소요되는 시간을 크게 줄이기 위한 자동레이블링 방식의 효과를 검증한다. 마지막으로, 제안하는 시스템의 실험에서 추가적으로 검증되어야 하는 부분과 함께 이를 개선하기 위한 향후 연구 계획에 대해 논의한다.